Professionalism Discourses and Neoliberalism in Teacher Education - Marom, Lilach; Ruitenberg, Claudia W. (Alberta Journal of Educational Research, 2019)
This article argues that discourses of “professionalism” can be used in K-12 teaching and teacher education, both in the service of neoliberal pressures and to push back against such pressures. By itself, the term “professionalism” is not evidence of either the spread of or resistance against neoliberalism, but considered in the context of a broader discourse, it may be used for both. The argument draws from Derrida’s discussion of the pharmakon, and Bourdieu’s discussion of symbolic capital. We argue that the concept of professionalism functions as a pharmakon in that it can be both toxic and medicinal, depending on how it is used, by whom, and to what ends. We take up Schinkel and Noordegraaf’s (2011) suggestion of enhancing Bourdieu’s framework of symbolic capital with that of professional capital. Considering professionalism as a kind of symbolic capital provides a critical lens on discourses of professionalism as both a help and a hindrance in K-12 teaching and teacher education. Both theoretical perspectives enable a critical questioning of discourses of professionalism, including for their constraining effect on greater diversity in professions. Cet article affirme que les discours sur le « professionnalisme » peuvent servir dans l’enseignement K-12 et dans la formation des enseignants, tant au service des pressions néolibérales que pour résister à ces pressions. En soi, le terme « professionnalisme » n’indique ni l’expansion du néolibéralisme ni l’opposition à ce phénomène; considéré dans un contexte élargi, le terme peut être employé dans les deux cas. Cet argument repose sur la discussion de Derrida sur le pharmakon et celle de Bourdieu sur le capital symbolique. Nous affirmons que le concept du professionnalisme fonctionne comme pharmakon dans le sens qu’il peut être ou bien un poison ou un médicament selon l’emploi qu’on en fait, la personne qui s’en sert et les raisons pour lesquelles on l’utilise. Nous faisons suite à la suggestion de Schinkel et Noordegraaf (2011) d’appuyer la notion du capital symbolique de Bourdieu avec celle du capital professionnel. Le fait de concevoir le professionnalisme comme une sorte de capital symbolique offre un angle critique pour étudier les discours proposant que le professionnalisme peut constituer un appui ou un obstacle dans l’enseignement K-12 et dans la formation des enseignants. Les deux perspectives théoriques permettent une remise en question des discours sur le professionnalisme, y compris de leur effet restrictif sur une plus grande diversité au sein des professions. Mots clés: néolibéralisme, formation des enseignants, professionalisme